The Semantic Displacement of the Sign and the Visual Formation of the Postmodern Theater (Al-Academy, 2018)
This research focuses on the field of theatrical production, and focuses on the semantic displacement of the sign in the visual formation of the theater show, so the research has been entitled: "The semantic displacement of the sign and the visual formation of the postmodern theater ". Its importance is to illustrate the aesthetics produced by the semantic displacement of the theatrical sign and it is specialized in postmodern theater. The purpose of the research can be delimited to revealing the aesthetic work of the semantic displacement of the sign and the visual formation in the postmodern theatre. The study temporal boundary is 2017 and the capital of Baghdad is its spatial boundaries. The research sample was "Striptease" play, which was presented on the National Theater in Baghdad in July 2017. The research included the theoretical framework which consists of two sections the first of which was concerned with the concept of semantic displacement in the artistic form, and the second section focused on the sign and the visual formation in the postmodern theater. The research came up with the most important results of the theoretical framework, followed by the research procedures and the identification of the study community, tools and methodology, leading to the analysis of the sample. The research reached a number of results that answered the research objective and problem. The most important results are: the semantic displacement establishes unexpected aesthetic dimensions for the sign through the relationship of the structural parts with each other in the visual formation and the displaced signs have more spacious areas in the visual theater show than in the dramatic textual script. The study ended with a list of sources.